2013
DOI: 10.3168/jds.2013-6945
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia in neonatal diarrheic calves depends on the degree of dehydration and the cause of the metabolic acidosis but does not require the presence of acidemia

Abstract: Hyperkalemia is a clinically important electrolyte imbalance in neonatal diarrheic calves that has previously been associated with skeletal muscle weakness and life-threatening cardiac arrhythmias. The aim of the present retrospective analysis was to identify risk factors for hyperkalemia in a convenience sample of 832 calves (≤ 21 d of age) with a clinical diagnosis of diarrhea admitted to a veterinary teaching hospital. Plasma potassium concentrations were most closely associated with parameters of dehydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 53 publications
6
57
0
Order By: Relevance
“…A similar increase after administration of sodium bicarbonate was not observed for D‐lactate in the present study. However, it needs to be emphasized that D‐lactate concentrations of most calves were within an established reference range for bucket‐fed calves of ≤3.96 mmol/L,66 which is in agreement with our previous findings that hyperkalemia in diarrheic calves is rarely associated with D‐lactic acidosis 4, 8. However given the fact that D‐lactate is only produced in minimal amounts in the methylglyoxal pathway in mammals,67 a therapeutic effect on D‐lactate concentrations could still be expected.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A similar increase after administration of sodium bicarbonate was not observed for D‐lactate in the present study. However, it needs to be emphasized that D‐lactate concentrations of most calves were within an established reference range for bucket‐fed calves of ≤3.96 mmol/L,66 which is in agreement with our previous findings that hyperkalemia in diarrheic calves is rarely associated with D‐lactic acidosis 4, 8. However given the fact that D‐lactate is only produced in minimal amounts in the methylglyoxal pathway in mammals,67 a therapeutic effect on D‐lactate concentrations could still be expected.…”
Section: Discussionsupporting
confidence: 91%
“…Based on anticipated mean and SD values for the plasma potassium concentration of 7.45 ± 1.28 mmol/L for the studied population based on data from 234 hyperkalemic calves of a previously published study,4 an alpha of 0.05 and a group size of 7, we calculated the power of the study to be 0.80.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classic papers stated that a 0.1 unit reduction in venous blood pH results in an increase of plasma K + of 0.3–0.5 mmol/L23 or 0.6 mmol/L 21. However, it was recently reported8 that this linear interrelation does not reflect the situation in diarrheic calves and that the presence of hyperkalemia depended on the nature of an existing acidosis but more importantly on the degree of dehydration. It was found that the presence of d ‐lactataemia in acidemic calves resulted in significantly lower odds for hyperkalemia but significantly higher odds for the presence of hypokalemia 8.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has shown that dehydration and concomitant impairment of renal function represents an important mechanism in the pathogenesis of hyperkalemia in such animals. Additionally, the presence of hyperkalemia was reported to be dependent on the nature of an existing acidosis in such that d ‐lactic acidosis is only rarely associated with a hyperkalemic state 7, 8…”
mentioning
confidence: 99%